A chemo-thermo-damage-transport model for concrete subjected to combined chloride-sulfate attack considering the effect of calcium leaching. (1st November 2021) - Wang, Penggang; Mo, Rui; Zhou, Xiangming; Xu, Jun; Jin, Zuquan; Zhao, Tiejun
Highlights: Calcium leaching effect is usually accompanied by cement matrix subjected to chloride-sulfate attack. Effects of calcium leaching and temperature on chloride transport in cement-based materials were simulated. Accelerated effect of combined chloride-sulfate attack on calcium leaching of cement-based materials was quantified. Abstract: Reinforced concrete structures can be seriously deteriorated under combined chloride-sulfate attack. To study the deterioration process of concrete under such condition, based on the chemo-physical–mechanical method, a coupled chemo-thermo-damage-transport model was proposed. Corrosive (i.e., acidic) environments and presence of chloride and sulfate ions in solution can promote the leaching and chemical transformation of solid-phase calcium from cement-based materials. Meanwhile, the change of temperature further affects the diffusivity and reaction rate of ions worsening the situation. Numerical results of the proposed model in this paper are in good agreement with the experimental results previously reported by Maes, suggesting that the proposed chemo-thermo-damage-transport model is reliable. During the experiment, the chloride distribution of Portland cement-based mortars immersed in 165 g / L NaCl and 50 g / L Na2 SO4 solution for 28 weeks at 20 and 35 °C was investigated. Results show that, without accelerated effect, the diffusivity of chloride in mortar increases with diffusion depth. After 180 days exposure, the degradation depth of the specimens immersed in the combined chloride-sulfate solution is almost 3 times of that of deionized water. By incorporating the temperature and calcium leaching effects into the numerical exploration, the conclusions can provide a technical guidance for the engineering practice of long-term chloride-sulfate attack.